Modeling of the resin transfer molding process including viscosity dependence with time and temperature - Soares, Laísa Luiz (2021)
Flow behavior inside the mold cavity of liquid molding processes such as resin transfer molding (RTM) is important information that is necessary to determine filling time and void formation. Most of the studies found in the literature use isothermal models with Newtonian fluids and constant viscosities. However, for some specific applications, the mold filling time dependence on temperature and the viscosity dependence on time and temperature must be considered to precisely predict the flow advance inside the mold. In this study, a viscosity model, that accounts for temperature and time dependence is coupled with a standard computational fluid dynamics (CFD) model to simulate the resin advance inside an RTM mold cavity. The model is simpler than similar methods that describe viscosity as a function of temperature and resin conversion. Nevertheless, the results show that the proposed model is capable of calculating flow advance, air and resin temperatures, and viscosity changes with time and temperature as expected in actual RTM and correlated processing of thick parts or with low injection pressure or high fiber content.